MENCAPAI KEUNGGULAN KOMPETITIF DENGAN BERFOKUS PADA KEPUASAN PELANGGAN - WIDAJANTI, ERNI (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2007)
ABSTRACT Globalization Economics have resulted progressively the increasing of strength of customer and market, and also affect at hyper competitions creation. Because with economics area globalization make economics without there is State boundary, so that facilitate entry of business perpetrator from within and abroad. To be able to stay in the middle of the hyper competition, of vital importance to company to be able to gratify its customer. For the shake of reaching of satisfaction of customer, company cope to yield a product which later, be offered to the market. But product which on the market by an unwelcome company sometimes market, this matter happened because market will look for product matching with their desire and requirement so that consumer or market satisfied. In effort reach excellence of competitive with focusing at satisfaction of customer, this matter have to represent the part of policy of company to create hand in glove relation with customer. And later, then this matter have to be inculcated in each company member individual to have desire serve customer eminently. Because this step can give customer benefit will satisfy because their requirement and desire fulfilled and satisfied customer of loyal to company. Keywords: customer satisfaction, global market, free trade